World checklist of flea-beetles of the genus Epitrix (Coleoptera: Chrysomelidae: Galerucinae: Alticini) - Bieńkowski, Andrzej O.; Orlova-Bienkowskaja, Marina J. (Zootaxa, 2017)
The world checklist of the genus Epitrix (Coleoptera: Chrysomelidae: Galerucinae: Alticini) is necessary, since many species of this genus are serious pests of potato and other Solanaceae, and since some species have been inadvertedly introduced from one continent to another and established. We have compiled the catalogue of all species described to date. There are 162 species and 11 subspecies in the world. The geographic distribution is indicated for each species.